Bioinspired graphene membrane with temperature tunable channels for water gating and molecular separation. Issue 1 (December 2017) - Liu, Jingchong; Wang, Nü; Yu, Li-Juan; Karton, Amir; Li, Wen; Zhang, Weixia; Guo, Fengyun; Hou, Lanlan; Cheng, Qunfeng; Jiang, Lei; Weitz, David; Zhao, Yong
Abstract Smart regulation of substance permeability through porous membranes is highly desirable for membrane applications. Inspired by the stomatal closure feature of plant leaves at relatively high temperature, here we report a nano-gating membrane with a negative temperature-response coefficient that is capable of tunable water gating and precise small molecule separation. The membrane is composed of poly(N -isopropylacrylamide) covalently bound to graphene oxide via free-radical polymerization. By virtue of the temperature tunable lamellar spaces of the graphene oxide nanosheets, the water permeance of the membrane could be reversibly regulated with a high gating ratio. Moreover, the space tunability endows the membrane with the capability of gradually separating multiple molecules of different sizes. This nano-gating membrane expands the scope of temperature-responsive membranes and has great potential applications in smart gating systems and molecular separation. The smart regulation of substance permeability is highly desirable for membrane separation technologies. Here, the authors design a poly(N -isopropylacrylamide)-grafted graphene oxide membrane with temperature tunable lamellar spaces, allowing for water gating and size-variable molecular separations.